A new record of species Loxostigma fimbrisepalum K. Y. Pan (Gesneriaceae Dumort) for the flora of Vietnam - Xuyen, Do Thi; Phuong, Vu Xuan (Academia Journal of Biology, 2012)
According to W. T. Wang et al., 1998 [9], the genus Loxostigma C. B. Clarke had about 7 species mainly distributed Asia. There were 4 Loxostigma species in Vietnam. This paper reported a new record of Loxostigma fimbrisepalum K. Y. Pan for the flora of Vietnam. Loxostigma fimbrisepalum is herbs, stems 50-100 cm, sparsely puberulent, or near glabrescen. Leaves opposite, spread along stem; leaf blade ovate to broadly elliptic, 8-20 3.0-8 cm, apex acuminate, sparsely puberulent on both of surfaces. Cymes branched 2-5, 5-18-flowered; peduncle 5-20 cm; bracts ovate to broadly ovate. Pedicel 1-2 cm. Calyx 5-sect from near base; segments equal; corolla white or light green, inside yellow-brown with purple spotted, ca. 4.0-4.8 cm long, outside sparsely pubescent, inside glabrous; Stamens 4, coherent at the anther; staminode ca. 2 mm long. Pistil 2.2-2.5 cm, glabrous. Style 1.1-1.3 cm. Capsule 5-6 cm. Seed appendages 1.1-1.2 mm. This species is closed to L. griffthii but differs by having as stem sparsely puberulent or near glabrous; corolla 4.0-4.8 cm long, white or light green; capsule 5-6 cm long. Voucher specimens were collected in Hoang Lien - Sa Pa national park and Hoang Lien - Van Ban Nature reserve, Lao Cai province; Nguyen Binh district, Cao Bang province, deposited in the Herbarium of the Institute of Ecology and Biological Resources, Hanoi, Vietnam (HN).